2020
DOI: 10.1073/pnas.2011660117
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired MXene-integrated colloidal crystal arrays for multichannel bioinformation coding

Abstract: Information coding strategies are becoming increasingly crucial due to the storage demand brought by the information explosion. In particular, bioinformation coding has attracted great attention for its advantages of excellent storage capacity and long lifetime. Herein, we present an innovative bioinspired MXene-integrated photonic crystal (PhC) array for multichannel bioinformation coding. PhC arrays with similar structure to Stenocara beetle’s back are utilized as the substrate, exhibiting properties of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 42 publications
0
53
0
Order By: Relevance
“…The integration of the human hand into these engineered functional systems can not only enhance sustainability but also increase the level of intelligence and controllability of these systems due to the direct involvement of human brains in the systems. The findings in this work will be of interest to communities of IR radiation related to biological systems, information decryption, human computer interface, and also the integration of biological components into functional systems ( 28 , 36 38 ).…”
mentioning
confidence: 91%
“…The integration of the human hand into these engineered functional systems can not only enhance sustainability but also increase the level of intelligence and controllability of these systems due to the direct involvement of human brains in the systems. The findings in this work will be of interest to communities of IR radiation related to biological systems, information decryption, human computer interface, and also the integration of biological components into functional systems ( 28 , 36 38 ).…”
mentioning
confidence: 91%
“…Recent studies have demonstrated the value of adenosine in neovascularization and fibrosis, which indicates that adenosine is an ideal candidate for wound healing [28,29]. In comparison, MXene, referring to transition metal carbides and nitride, is an emerging two-dimensional material family that exhibits tremendous potential in various fields, including energy storage [30,31], catalysis [32,33], biomedical applications [34][35][36], etc. [37].…”
Section: Introductionmentioning
confidence: 99%
“…Among those electrical conductors, MXenes [20,21], as one class of two-dimensional early-transition metal carbides/carbonitrides, have emerged with widespread attention due to their fascinating properties, such as large hydrophilic surfaces and excellent electrical/thermal conductivity. These MXenes have also been widely and successfully assembled into two-dimensional materials and even in three-dimensional frameworks to improve their functions [22][23][24]. Although with many successes, most of the MXene-derived electronic systems are with simple structures or morphologies because of their comparatively simple preparation process, which might restrict their performances under complex situations.…”
Section: Introductionmentioning
confidence: 99%